Use of recombinant factor VIIa in a preterm infant with coagulopathy and subdural hematoma - BİLGEN, HÜLYA SELVA (TAYLOR & FRANCIS LTD, 2007)
Activated recombinant factor VIIa was administered to a preterm infant with bleeding diasthesis and a huge subdural hematoma that could not be controlled by the blood products. The coagulation tests were normalized the following day. Recombinant factor VIIa can be a choice in selected cases with intractable bleedings unesponsive to conventional replacement therapy.
Keywords: factor VIIa; preterm; bleeding diasthesis; ACTIVATED FACTOR-VII; HEMORRHAGE; PHARMACOKINETICS; MANAGEMENT; SURGERY; RFVIIA